2006
DOI: 10.1002/pa.39
|View full text |Cite
|
Sign up to set email alerts
|

Strategic postures of political marketing: an exploratory operationalization

Abstract: In contrast to most political marketing theories which imply that such concepts as ‘voter‐orientation’ or ‘voter‐centric political management’ are trivial and uni‐dimensional, this article will take its starting point from an alternative perspective. It draws on the concept of political marketing ‘postures’, i.e. a multi‐faceted conceptual entity, based on varied dimensions of political marketing orientations. The main duality consists of the constructs of ‘leading’ and ‘following’, with an auxiliary (and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
1
16
0
3
Order By: Relevance
“…Candidates have to balance elements of continuity and change, as voters expect some aspects of the candidate's appeal to be consistent, and at the same time expect them to be responsive to new preferences (Butler & Collins 1996). Others have indicated that candidates and political parties have started adopting votercentric or market-orientated approaches (Henneberg 2006). Further, many citizens vote retrospectively, looking to past statements, behaviours and performance to reach a voting decision; thus, information from the past is used as a guide to making projections (Boiney & Paletz 1991).…”
Section: Issue Inconsistency and The Expectation-disconfirmation Paramentioning
confidence: 98%
“…Candidates have to balance elements of continuity and change, as voters expect some aspects of the candidate's appeal to be consistent, and at the same time expect them to be responsive to new preferences (Butler & Collins 1996). Others have indicated that candidates and political parties have started adopting votercentric or market-orientated approaches (Henneberg 2006). Further, many citizens vote retrospectively, looking to past statements, behaviours and performance to reach a voting decision; thus, information from the past is used as a guide to making projections (Boiney & Paletz 1991).…”
Section: Issue Inconsistency and The Expectation-disconfirmation Paramentioning
confidence: 98%
“…They offer an inspirational reinterpretation in marketing terms of Kirchheimer's previous study (1966) of transformational processes at work in political parties and party systems. Henneberg (2006a) claims that the internal character of many political parties, revealed by electoral manifestos, communication methods, and practical targeting approaches towards voters, is still linked to their inherent political ideology. We follow his claim and argue that the ideological profiles of political parties, whether dominant or marginal, may sometimes be supplemented by internal or external party sources.…”
Section: Discussionmentioning
confidence: 99%
“…Různé typy politických stran a kandidátů přitom vstupují běžně do politiky a voleb s odlišnými postoji a cíli, ovlivněnými jak jejich vnitřně přijímanou ideologií, tak i vztahem k voličům prostřednictvím volební nabídky. To se projevuje i v jejich chování a nastavené marketingové strategii (Henneberg 2006a;2006b;Ormrod, Henneberg a O'Shaughnessy 2013).…”
Section: Dosavadní Stav Poznáníunclassified
See 2 more Smart Citations